Case Report: Tadpole pupil and concurrent migraine in an adolescent patient is a novel correlation - Alexander Scheid; Alexander Scheid; Rebecca Lise Gammelgaard Henneberg; Jonas Kjeldbjerg Hansen; Jonas Kjeldbjerg Hansen (Frontiers Media S.A., 2024)
BackgroundTadpole pupil is a rare phenomenon characterized by a brief and irregular deformation of the pupil caused by segmental contraction of the iris dilator muscle. It is most prevalent in adult women and is, in these cases, often associated with migraine.Case presentationWe present a unique case of a 16-year-old girl who presented with recurrent episodes of tadpole pupil and vestibular migraine. This association has not been previously demonstrated in pediatric patients. During a thorough clinical examination, a thyroid carcinoma was found which due to its localization was not causative of the tadpole pupil and was considered an incidental finding.ConclusionsThe association between migraine and tadpole pupil in this patient, which has not previously been described in pediatric patients, adds to the demographics of tadpole pupil. A possible pathophysiological link between the two conditions is discussed but further research is needed to understand the pathophysiology underpinning it.